2014
DOI: 10.1167/iovs.13-13707
|View full text |Cite
|
Sign up to set email alerts
|

Drug and Gene Delivery to the Back of the Eye: From Bench to Bedside

Abstract: The SERC provided a diverse group of approximately 150 scientists and physicians representing industry and academia from 14 countries with a unique opportunity to explore the latest approaches to drug and gene delivery to the posterior segment of the eye. Unlike the 2009 SERC meeting, which focused on novel drug delivery platforms while elucidating the anatomic barriers to reach the posterior segment, 1 the most recent meeting explored strategies for bypassing ocular barriers using novel materials, nanoparticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 72 publications
0
75
0
Order By: Relevance
“…Therefore, ocular pharmacokinetics relies on animal models, mostly rabbits. Recently, the rabbit eye has been criticized for being a poor model of the human eye (Laude et al, 2010;Rowe-Rendleman et al, 2014). Therefore, we investigated all available intravitreal pharmacokinetic data in rabbits (del Amo et al, 2015) and humans (this review) and derived the pharmacokinetic parameters (clearance, volume of distribution) to compare systematically intravitreal pharmacokinetics in man and rabbit.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ocular pharmacokinetics relies on animal models, mostly rabbits. Recently, the rabbit eye has been criticized for being a poor model of the human eye (Laude et al, 2010;Rowe-Rendleman et al, 2014). Therefore, we investigated all available intravitreal pharmacokinetic data in rabbits (del Amo et al, 2015) and humans (this review) and derived the pharmacokinetic parameters (clearance, volume of distribution) to compare systematically intravitreal pharmacokinetics in man and rabbit.…”
Section: Introductionmentioning
confidence: 99%
“…Intravitreal injections have been considered the preferred route of drug delivery to the eye during the past 2 decades, and they are the most effective drug delivery method for the retina. [4][5][6][7] Compared with systemic administration, this method has the advantages of localizing the drug effect with higher drug concentrations in the vitreous and retina. It is commonly performed by injecting a drug suspension or solution into the vitreous cavity in the center of the eye via pars plana using a 30 G needle.…”
Section: Introductionmentioning
confidence: 99%
“…There are solid or hollow microneedles available, which were initially developed for transdermal application. Microneedles can deliver free or encapsulated drugs with minimal invasion and may avoid the safety concerns associated with repeated intravitreal applications (Rowe-Rendleman et al 2014). Based on animal studies, it was reported that insertion site disappears 1 h after microneedle injection .…”
Section: Microneedlesmentioning
confidence: 99%